Epidemiology of tattoo skin disease in captive common bottlenose dolphins (Tursiops truncatus): Are males more vulnerable than females?. Issue 4 (2nd October 2018) - Van Bressem, Marie-Françoise; Van Waerebeek, Koen; Duignan, Pádraig J.
ABSTRACT: Clinical and epidemiological features of tattoo skin disease (TSD) are reported for 257 common bottlenose dolphins held in 31 facilities in the Northern Hemisphere. Photographs and biological data of 146 females and 111 males were analyzed. Dolphins were classified into three age classes: 0–3 years, 4–8 years, and older than 9 years. From 2012 to 2014, 20.6% of the 257 dolphins showed clinical TSD. The youngest dolphins with tattoo lesions were 14 and 15 months old. TSD persisted from 4 to 65 months in 30 dolphins. Prevalence varied between facilities from 5.6% to 60%, possibly reflecting variation in environmental factors. Unlike in free-ranging Delphinidae, TSD prevalence was significantly higher in males (31.5%) than in females (12.3%). Infection was age-dependent only in females. Prevalence of very large tattoos was also higher in males (28.6%) than in females (11.1%). These data suggest that male T. truncatus are more vulnerable to TSD than females, possibly because of differences in immune response and susceptibility to captivity-related stress.